Central African Republic : 2018 Article IV Consultation, Fifth Review under the Extended Credit Facility Arrangement, and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2018)
The Central African Republic (C.A.R.) is a fragile state with an unstable security environment and widespread poverty. Macroeconomic conditions have stabilized following the 2013 crisis: growth has resumed, inflation has declined, domestic revenues have recovered, and debt ratios have decreased. The government's economic strategy is supported by an arrangement under the Extended Credit Facility (ECF)-launched in July 2016-with total access of SDR 133.68 million (120 percent of quota). Program performance has been satisfactory. All end-June 2018 quantitative and continuous performance criteria were met. Discussions focused on the 2019 budget, policy responses to a higher global oil price, and reforms to improve public financial management and governance. The program is supported by union-level efforts to maintain an appropriate monetary policy stance, build up regional reserves, and promote financial sector stability.